Optimalisasi Penerapan Komunikasi SBAR saat Serah Terima Pasien antar Shift Keperawatan - Ayu My Lestari Saragih; Enie Novieastari (Jurnal Keperawatan Silampari, 2022)
This study aims to optimize the application of SBAR communication during handovers between nursing shifts. This research method is a case study with a situation analysis. The results showed that the application of SBAR communication was not optimal when handing over patients between nursing shifts. Innovations are developed by making additional recommendations for SBAR SOPs and monitoring and evaluation drafts referring to the literature. A trial of money filling can be carried out. In conclusion, it is necessary to have a supervisor (Karu) whose function is to direct nurses, especially in the implementation of the handover, so that the nurse will carry out the weigh-in following the direction of the head of the room and the SOP that applies in the room regarding the implementation of the handover. Keywords: Head of Room, SBAR Communication, Supervision